How does dietary intervention (specifically reducing dairy and high-sugar foods) impact acne progression : A Systematic Review - Elvira Miranda; Khairunnisa (The International Journal of Medical Science and Health Research, 2025)
Introduction: Acne vulgaris is a common chronic inflammatory skin condition, and the role of diet in its management is of growing interest. Diets with a high glycemic load and dairy consumption have been implicated, but the evidence for their impact on acne progression remains inconsistent. This systematic review aims to synthesize and evaluate evidence from recent studies to determine the effect of reducing dairy and high-sugar foods on acne severity. Methods: This review followed the PRISMA 2020 guidelines. A systematic search was conducted across PubMed, Semantic Scholar, Springer, Google Scholar, and Wiley Online Library for randomized controlled trials (RCTs) and systematic reviews published since 2015. Studies were included if they investigated dietary interventions involving dairy or sugar reduction in participants with acne vulgaris and measured quantitative changes in acne severity. A total of 20 studies met the eligibility criteria for inclusion. Results: The findings demonstrate a clear divergence in evidence. Interventions involving low-glycemic load or index diets consistently showed significant improvements in acne. Of the studies examining this approach, 11 reported a statistically significant reduction in acne severity, including decreased lesion counts and improved acne grades. In contrast, the evidence for dairy was primarily associative. Three studies reported a positive association between dairy intake and acne risk, but others found the evidence to be mixed or inconclusive, particularly for whey protein. The link was often characterized by heterogeneity and potential bias. Discussion: The evidence strongly supports low-glycemic diets as an effective intervention for acne, likely due to the modulation of inflammatory pathways. The role of dairy is less definitive and seems to be based on association rather than established causality from interventional trials. The duration of intervention, typically 8-12 weeks, appears crucial for observing clinical benefits from dietary changes. Conclusion: Dietary interventions focusing on reducing glycemic load are a viable and effective strategy for managing acne vulgaris. The role of dairy remains ambiguous and requires a more personalized approach. These findings support the integration of evidence-based nutritional counseling into standard dermatological care for acne.